Import Components and Import Multipliers in Australian Economy: World Input-Output Analysis - Muchdie, M.; Kurniawan, H. (International Journal of Economics and Financial Issues, 2018)
This article analysis on import components and import multipliers, using Australian input-output tables 2000, 2005, 2010 and 2014. The results showed that firstly, Australian import components of input were, on average, less than 20 per cent; meaning that input that locally provided were more than 80 per cent. Australian import of input had increased significantly from US 47,122 million in 2000 to US 14,616 million in 2014. Secondly, Australian imports have been dominated by Sector-8, Sector-13, Sector-24, Sector-25, and Sector-26. Thirdly, Australian imports have been dominated by the USA, Japan, United Kingdom, China and Germany. During 2000-2014, import from Canada, Japan, UK and the USA had declined, but import from China had significantly increased. Finally, highest sectoral import multipliers occurred in Sector-5, Sector-22, Sector-29, Sector-30, Sector-31, and Sector-32, but there was no significant different of import multipliers for country origin of import. Keywords: import components, sectoral import multipliers, spatial import multipliers. JEL Classifications: C67, D57, F17.